Enhanced chemiluminescence of cerium(IV)–Tween 85 system and the analytical application. (20th December 2012) - Li, Shifeng; Qian, Li; Zhu, Yan; Liu, Manman; Gao, Yinping; Ni, Yonghong
ABSTRACT The oxidation reaction between cerium(IV) and Tween 85 in sulfuric acid medium produced weak chemiluminescence (CL). In this paper, it was found that citrate could strongly enhance the CL of cerium(IV)–Tween 85–polyphenol system. Based on studies of ultraviolet–visible spectra and CL spectra, the CL enhancement mechanism had been proposed. It was surmised that the light emission was from an excited oxygen molecular pair O2(1Δg)O2(1∑g–). The maximum emission wavelength was about 478 nm. The effects of 17 amino acids and 29 organic compounds on cerium(IV)–Tween 85–citrate CL were investigated by a flow injection procedure. This study showed the present system had a wide application for the determination of these compounds. Copyright © 2012 John Wiley & Sons, Ltd.